2009
DOI: 10.1093/esr/jcn077
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents Coordinate Their Work Schedules? A Comparison of Dutch, Flemish, and Italian Dual-Earner Households

Abstract: As a consequence of the rising number of dual earner households, many contemporary couples in Europe face two potentially conflicting job schedules when figuring out how to allocate their time over a week. In this article we study how dual-earner couples with children organise their working time in Belgium, Italy and The Netherlands. We place working time coordination explicitly in a comparative framework to allow cross-country differences in time scheduling mechanisms to be revealed. We define working time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 26 publications
3
20
0
3
Order By: Relevance
“…Previous research on the timing of parental work and child care has mainly focused on the care that parents themselves provide (Carriero et al 2009;Täht and Mills 2012). We extended this line of research by considering nonparental care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on the timing of parental work and child care has mainly focused on the care that parents themselves provide (Carriero et al 2009;Täht and Mills 2012). We extended this line of research by considering nonparental care.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands, however, different labor legislation and regulations exist (Täht and Mills 2012), which may make Dutch nonstandard work more suitable for dividing care between two nonstandard working parents. Indeed, previous research has indicated that Dutch parents tend to de-synchronize their working hours, whereas parents from other countries tend to do the opposite (Carriero et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies used preference for togetherness as a proxy for estimating the importance of time together in families (Carriero, Ghysels, & Van Klaveren, 2009;Hamermesh, 2000;Klaveren & Brink, 2007). However, they did not address directly the interrelation between time spent together in couples and marital quality.…”
Section: Measurementsmentioning
confidence: 99%
“…Finding a correlation between the work timing estimate and the demand for child care is interesting from a policy perspective: more flexible working times could become one of the ingredients of a policy mix such that the focus is more on the work-family balance. Finding this balance is now often difficult for spouses in dual-earner households because labor market rigidities restrict them in the timing of their working hours (Carriero, Ghysels and Van Klaveren (2009)). …”
mentioning
confidence: 99%